2018
DOI: 10.1002/ejic.201800029
|View full text |Cite
|
Sign up to set email alerts
|

Copper(I)–Dioxygen Reactivity in the Isolated Cavity of a Nanoscale Molecular Architecture

Abstract: Copper(I) and copper(II) complexes supported by a bulky tetradentate N 4 ligand, [Cu I (TIPT 3 tren)(CH 3 CN)]ClO 4 (1) and [Cu II (TIPT 3 tren)Cl]BF 4 (2), were synthesized and characterized, where TIPT is 2,2′′,6,6′′-tetraisopropyl-1,3′:5′,1′′-terphenyl and tren is tris(2-aminoethyl)amine. The copper(II) chloride complex 2 exhibits a trigonal-bipyramidal structure, as usually observed for the tren ligand system, in which the chloride ligand occupies an axial position and is encapsulated in an isolated cavity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…Superoxide complex 4 was X‐band EPR‐silent at 77 K. The 1 H NMR spectrum of 4 in [D 6 ]acetone at –85 °C shows signals in the paramagnetic region, –25 to 50 ppm (Figure S7, Supporting Information). These results confirm the triplet ground state of 4 as in the cases of other end‐on superoxide copper(II) complexes so far been reported , , , …”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Superoxide complex 4 was X‐band EPR‐silent at 77 K. The 1 H NMR spectrum of 4 in [D 6 ]acetone at –85 °C shows signals in the paramagnetic region, –25 to 50 ppm (Figure S7, Supporting Information). These results confirm the triplet ground state of 4 as in the cases of other end‐on superoxide copper(II) complexes so far been reported , , , …”
Section: Resultssupporting
confidence: 90%
“…As is mentioned in Section Introduction, we have found that the reaction of copper(I) complex 1′ supported by TIPT 3 tren and dioxygen gave a mixture of copper(II)‐superoxide complex 4′ (type A ) and copper(III)‐(side‐on)peroxide complex 5′ (type C ) . In the case of copper(I) complex 1 supported by TIPT 2 aped, there is no absorption feature ascribable to a side‐on peroxide copper(III) complex (type C ) around 550 nm.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…[11] Thus,t he study of synthetic cupric superoxide model complexes to further understand their structures, physical-spectroscopic properties,a nd correlated reactivity toward the hydroxylation of substrates containing strong CÀ Hb onds is of considerable interest in catalysis.Ty pically,t hese primary copper-dioxygen superoxide model species [11,15,16] are difficult to study due to their tendency to form secondary Cu 2 -O 2 adducts (that is, m-1,2peroxo-dicopper(II), side-on peroxodicopper(II), or bis-moxodicopper(III) complexes) in solution. Researchers have been able to prevent the formation of 2:1C u:O 2 adducts through ligand design;the addition of as econdary coordination sphere of sterically bulky groups [17][18][19][20][21] or hydrogenbonding (H-bonding) moieties [22,23] allows for the stabilization of cupric superoxide complexes.T hese H-bonding effects, noted for superoxide and peroxide stabilization via amide and amine H-bonds, [24,25] play ar ole similar to that of the acidic (thus H-bonding) O 2 -binding pocket in the single coppercontaining formylglycine-generating enzyme (FGE). [26] However,t here have been limited reports on how such factors influence the electrophilic reactivity of cupric superoxide complexes toward OÀHo rC ÀHs ubstrates, [11,15,22,23,27] particularly those of biological interest.…”
mentioning
confidence: 99%